AI-POWERED HEALTHCARE REVOLUTION: AN EXTENSIVE EXAMINATION OF INNOVATIVE METHODS IN CANCER TREATMENT - Murad Khan; Ashish Shiwlani; Muhammad Umer Qayyum; Abdul Mannan Khan Sherani; Hafiz Khawar Hussain (BULLET : Jurnal Multidisiplin Ilmu, 2024)
Abstract: This study examines the various ways that artificial intelligence (AI) is being used into the field of cancer medicine, with an emphasis on innovative techniques and advances in healthcare. The article, titled "AI Healthcare and Novel Approaches in the Field of Cancer Medicine," explores how AI is revolutionizing a number of fields, including population health management, clinical decision support, drug discovery, pathology analysis, diagnostic imaging, predictive modeling, and predictive modeling. The essay starts out by exploring the revolutionary role that artificial intelligence (AI) is playing in diagnostic imaging, where algorithms are demonstrating exceptional accuracy in identifying anomalies, especially in MRIs, CT scans, and mammograms. The tailoring of cancer treatments based on unique molecular profiles, bringing in a new age of targeted therapies, and minimizing side effects are the main themes that arise from precision oncology. AI-powered clinical decision support systems analyze a variety of patient data to improve the decision-making process for medical personnel. As a crucial component of cancer medicine, predictive modeling provides insights into disease development, therapeutic responses, survival prognostication, and the identification of high-risk patients. The study highlights how AI can improve clinical trials, speed up drug research and development, and change pathology and histology analysis to provide more precise cancer diagnosis.